Diversification and Cooperation Strategies in a Decarbonizing World - Peszko, Grzegorz; van der Mensbrugghe, Dominique; Golub, Alexander (World Bank, Washington, DC, 2020)
Fossil fuel importers can apply various climate and trade taxes to encourage fossil fuel–dependent countries to cooperate on climate mitigation, and fossil fuel–dependent countries can respond with alternative diversification and cooperation strategies. This paper runs macroeconomic model simulations of alternative strategies that the global community and fossil fuel–dependent countries can pursue to encourage and enable their participation in a global low-carbon transition. The following are the findings from the simulations. (i) Fuel importers’ unilateral carbon taxes capture fossil fuel–dependent countries’ resource rents and accelerate their emission-intensive diversification. (ii) Border taxes on the carbon content of imports from fossil fuel–dependent countries do not induce comprehensive cooperation, but broader trade sanctions do. (iii) Cooperative wellhead carbon taxes can achieve cooperation without trade wars. (iv) Lower-income fossil fuel–dependent countries with large untapped reserves need additional incentives and enablers to cooperate and diversify into low-carbon assets. (v) Incentives to cooperate are misaligned between different fossil fuel–dependent countries and between owners of different fuels. (vi) The strategies that maximize consumption and growth in fossil fuel–dependent countries reduce the value of assets in extractive and heavy industries. (vii) Asset diversification is a robust, long-term strategy but faces the tragedy of the horizon.